Character Strengths of Czech Army Excellent Officers as Perceived by Cadets and Soldiers Serving in Reconnaissance Units - Heřman, Ondřej; Mac Gillavry, David William; Höschlová, Eva; Ullrich, David (Military medicine, 2024)
INTRODUCTION: A deeper understanding of personality specifics in military personnel may increase the efficacy of health care professionals in this field. Changes in modern warfare require army officers to make decisions in complicated situations with increasing levels of autonomy. Character is traditionally regarded as a key quality in these dynamics. However, it remains unclear which character strengths are conducive to effective leadership in the military. The present study aims at mapping Czech Army cadets' and professional soldiers' perceptions of the character strengths of those officers, who they consider the best they served under. The study also examined how these perceptions vary across soldiers at different stages of their careers and how much they overlap with the same soldiers' ratings of their own strengths. In addition, a regression analysis, to outline combinations of strengths for various aspects of character-based leadership, was performed. MATERIALS AND METHODS: Respondents (N = 199) were recruited from three different subpopulations of the Czech Army-serving members of two reconnaissance units (N = 38), and 1st (N = 81) and 5th (N = 80) year cadets at the University of Defense. They rated the character strengths of chosen officers and themselves on the Character Strengths Leadership Inventory and the Values in Action Inventory of Strengths Revised. This study was approved by the units' commanding officer and the representatives of the University of Defense. RESULTS: Subordinates rated honesty, leadership, perspective, teamwork, fairness, creativity, love of learning, and zest highest in their chosen officers. These officers' mean profiles strongly correlated in all the three groups (rs = .82-.86). The mean correlation between officers' and respondents' self-reported strengths was not strong (rs = .18). Multiple regression models of the perception of an officer's success, success of their team, them as a leadership example, and them as having a good character, most frequently, involved fairness, honesty, kindness, and social intelligence, while forgiveness was negatively associated with these parameters. CONCLUSIONS: The present study achieved its aims. First, it suggests the officers' character strengths that tend to be most valued by their subordinates among Czech Army cadets and soldiers serving in reconnaissance units. Second, the strong overlap of best officers' character profiles in all groups suggests that this perception may remain stable throughout a soldier's career. Third, the relationship between chosen officers' and respondents' self-reported strengths was negligible, suggesting that the perception of officer's strengths may not be an individual's projection. Fourth, regression models of character-based leadership proposed a combination of character strengths that may contribute to the officer's perceived efficacy. Compared to other studies, the sample included both cadets and military professionals with a proportional number of females being included. These results imply that health care practitioners working with military clients may benefit from the acknowledgment of their specific character strengths, most notably honesty and fairness, while providing care to this population.
Keywords: Female; Military Personnel; charakter; vedení války; ženské pohlaví; Česká republika; Humans; lidé; Czech Republic; Self Report; zpráva o sobě; ozbrojené síly; Warfare; Character